Central Composite Designed Fast Dissolving Tablets for Improved Solubility of the Loaded Drug Ondansetron Hydrochloride - Thalluri, Chandrashekar; Amin, Ruhul; Mandhadi, Jithendar Reddy; Gacem, Amel; Emran, Talha Bin; Dey, Biplab Kumar; Roy, Arpita; Alqahtani, Mohammed S.; Refat, Moamen S.; Safi, Sher Zaman; Alsuhaibani, Amnah Mohammed (BioMed research international, 2022)
Ondansetron tablets that are directly compressed using crospovidone and croscarmellose as a synthetic super disintegrant are the subject of this investigation. A central composite, response surface, randomly quadratic, nonblock (version 13.0.9.0) 32 factorial design is used to optimize the formulation (two-factor three-level). To make things even more complicated, nine different formulation batches (designated as F1–F9) were created. There were three levels of crospovidone and croscarmellose (+1, 0, -1). In addition to that, pre- and postcompressional parameters were evaluated, and all evaluated parameters were found to be within acceptable range. Among all postcompressional parameter dispersion and disintegration time, in vitro drug release experiments (to quantify the amount of medication released from the tablet) and their percentage prediction error were shown to have a significant influence on three dependent variables. Various pre- and postcompression characteristics of each active component were tested in vitro. Bulk density, tap density, angle of repose, Carr’s index, and the Hausner ratio were all included in this analysis, as were many others. This tablet’s hardness and friability were also assessed along with its dimension and weight variations. Additional stability studies may be conducted using the best batch of the product. For this study, we utilised the Design-Expert software to select the formulation F6, which had dispersion times of 17.67±0.03 seconds, disintegration times of 120.12±0.55 seconds, and percentage drug release measurements of 99.25±0.36 within 30 minutes. Predicted values and experimental data had a strong correlation. Fast dissolving pills of ondansetron hydrochloride may be created by compressing the tablets directly.